ANALISA LAJU KOROSI PIPA SCH 40 SEAMLESS DENGAN VARIASI MEDIA PENGKOROSIAN AIR PAYAU DAN AIR LAUT - Maitimu, Cindy Gabriel; Loppies, Leslie S.; Pellu, Denny Ismail; Huka, Graciadiana I (Jurusan Teknik Mesin, 2024)
Metals, especially steel, are widely used in various industrial applications due to their strength and durability. However, corrosion is a significant drawback that can shorten the life of the material. This research aims to analyze the corrosion rate of SCH 40 seamless pipes with a variety of corrosion media: brackish water, sea water, aquadess, NaCl solution, and oxygen, in conditions without paint coating and with paint coating. The research method uses the weight loss method according to the ASTM G102-89 standard, where the corrosion rate is measured in millimeters per year (mmpy) by calculating the difference in pipe weight before and after immersion. The results show that the corrosion rate without paint coating is: brackish water 0.00016 mmpy, sea water 0.00014 mmpy, aquadess 0.00016 mmpy, NaCl 0.00015 mmpy, and oxygen 0.0000045 mmpy. Seawater showed the lowest corrosion rate, possibly due to the formation of a passive protective layer. Oxygen had the lowest corrosion rate, indicating that oxygen alone does not cause significant corrosion without moisture. With paint coating, the pipe corrosion rate becomes: brackish water 0.00000125 mmpy, sea water 0.00000125 mmpy, aquadess 0.00000268 mmpy, NaCl 0.00000107 mmpy, and oxygen 0.00000125 mmpy. The use of paint coatings significantly reduces the rate of corrosion, especially in corrosive media such as brackish water, sea water and salt solutions. These results emphasize the importance of paint coatings to extend the service life of pipes by reducing the speed of corrosion. Key words: corrosion, seamless pipe, paint coating, corrosion media, corrosion rate, weight loss method